2015
DOI: 10.1111/pbr.12262
|View full text |Cite
|
Sign up to set email alerts
|

Wheat spike fertility: inheritance and relationship with spike yield components in early generations

Abstract: In wheat, grain number is considered as the product of spike dry weight (SDW) and the number of grains per unit of SDW, that is an indicator of spike fertility (SF). The aim of this study was to determine the heritability of SF and the effect of early selection for high SF on its relationship with other spike yield components. Two field experiments were conducted in the south‐eastern Pampas (Argentina) with 400 F2 and F2:3 families obtained from two crosses between varieties with contrasting SF (PIG/SSN and B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 20 publications
8
42
0
Order By: Relevance
“…Water stress during meiosis significantly reduced ( p < 0.01) seed set compared to non-stressed plants. For the 46 tested wheat genotypes, the mean seed set under non-stressed conditions was 68%, because not all fertile florets had the potential of setting into grains, similar result has been previously reported in Ferrante et al (2013) where increase in nitrogen availability affected the number of fertile florets and the number of grains the florets produce at maturity - the relationship of wheat spike fertility and seed set was also reported by Martino et al (2015). Under stressed conditions the mean seed set was reduced to 52%.…”
Section: Resultssupporting
confidence: 81%
“…Water stress during meiosis significantly reduced ( p < 0.01) seed set compared to non-stressed plants. For the 46 tested wheat genotypes, the mean seed set under non-stressed conditions was 68%, because not all fertile florets had the potential of setting into grains, similar result has been previously reported in Ferrante et al (2013) where increase in nitrogen availability affected the number of fertile florets and the number of grains the florets produce at maturity - the relationship of wheat spike fertility and seed set was also reported by Martino et al (2015). Under stressed conditions the mean seed set was reduced to 52%.…”
Section: Resultssupporting
confidence: 81%
“…In a paper that was just published, Mirabella et al () reported new results confirming wide variation in fruiting efficiency among modern cultivars and revealing that this variation was consistently larger than GxE interaction.…”
Section: Genetic Variation In Fruiting Efficiency Within Elite Germplasmmentioning
confidence: 88%
“…In a paper that just became available, Martino et al () also found that fruiting efficiency exhibited transgressive segregation and would be reasonably heritable.…”
Section: Genetic Variation In Fruiting Efficiency Within Elite Germplasmmentioning
confidence: 99%
“…The environmental effects on spikes are very likely to be compensated by the modification of other parts within the same plant. The influence on spike components is possibly compensated by the responses of other components within the same spike (Dreccer et al, 2009;Gaju et al, 2009;Gonzalez et al, 2011;Lazaro & Abbate, 2012;Reynolds et al, 2012;Nagel et al, 2013;Martino et al, 2015). Therefore, grain yield-related traits do not always reflect the overall information concerning environmental effects, because the environmental influence on the grain weight per spike is often partly offset by 'compensations'.…”
Section: Discussionmentioning
confidence: 99%